Pertussis epidemiology and effect of vaccination among diagnosed children at Vietnam, 2015‐2018. (15th April 2020) - Pham, Nhung T. H.; Le, Nhan D. T.; Le, Ngai K.; Nguyen, Khoa D.; Larsson, Mattias; Olson, Linus; Tran, Dien M.
Abstract: Aim: To evaluate effect and costs of pertussis vaccination at Vietnam National Children's Hospital. Methods: Pertussis cases were defined by positive laboratory tests of children under 5 years January 2015‐June 2018, and data on patient characteristics, clinical data and hospitalisation costs were collected through patient records. Results: Of 909 inpatients, 400 (44%) were <2 months, the age for first DPT vaccination, and mechanical ventilation was more common than in children >2 months (9% vs 4%, OR = 2.3, CI 1.3‐3.9), as well as persistent cough (99%), violent cough (87%) and pneumonia (91%). Comparing non‐vaccinated (172 cases, 19%) and DPT vaccinated patients >2 months of age hospitalisation was 106‐fold higher (149.6 vs 1.39 per 100 000 population), and proportion of severe patients, length of hospital stay and hospitalisation costs were significantly greater (23.9% vs 12.8%; 13 vs 10 days; 826 USD vs 582 USD, CI 23‐423, P  = .03). Conclusion: Incidence and proportion of complications among under 2‐month infants were higher than in older patients. DPT vaccination protects children from pertussis infection, and in case of pertussis infection decreases severity. Results indicate that the Ministry of Health should consider adding a booster vaccine for pregnant women in an extended vaccination programme.